Comparison of different techniques for calcium hydroxide removal from the mesial root canals of mandibular first molars - Nasrin Roghanizad; Faezeh Alaie Kerahrodi; Sohrab Tour Savadkouhi; Milad Moradi (Journal of Dental Materials and Techniques)
Objective: This study aimed to compare the efficacy of passive ultrasonic irrigation (PUI), EndoActivator, Sonic Air, and hand filing in removing calcium hydroxide (CH) from the mesial root canals of mandibular first molars.Methods: The mesiobuccal and mesiolingual root canals of 40 extracted mandibular first molars were instrumented and filled with CH paste. The specimens were randomly assigned to four groups (n = 20) based on the CH removal technique: (1) PUI, (2) EndoActivator, (3) Sonic Air, and (4) hand K-file (#25). Irrigation was performed with 5.25% sodium hypochlorite (NaOCl), 17% ethylenediaminetetraacetic acid (EDTA), and a final rinse with distilled water. Residual CH was assessed using the Van der Sluis method under a stereomicroscope and analyzed with Kruskal-Wallis and Mann-Whitney U tests (α=0.05).Results: There were significant differences in residual CH among groups in both mesiobuccal (P<0.001) and mesiolingual (P=0.002) canals. In the mesiobuccal canal, PUI and EndoActivator were equally effective (P>0.05) and superior to Sonic Air and hand filing (P<0.05), whereas Sonic Air significantly outperformed hand filing (P<0.05). In the mesiolingual canal, no significant difference was found between PUI, EndoActivator, and Sonic Air (P>0.05), but all methods were significantly more effective than hand filing for CH removal (P<0.05).Conclusions:  PUI, EndoActivator, and Sonic Air systems were significantly more effective than hand filing in removing CH from the mesial root canals of extracted mandibular first molars. Among the experimental groups, the efficacy ofPUI and EndoActivator were better than Sonic Air in CH removal from mesiobuccal root canals.